2012
DOI: 10.1371/journal.pone.0049447
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Blood-Derived Mesenchymal Stem Cells Promote Vascular Growth In Vivo

Abstract: Stem cell therapies are promising strategies to regenerate human injured tissues, including ischemic myocardium. Here, we examined the acquisition of properties associated with vascular growth by human umbilical cord blood-derived mesenchymal stem cells (UCBMSCs), and whether they promoted vascular growth in vivo. UCBMSCs were induced in endothelial cell-specific growth medium (EGM-2) acquiring new cell markers, increased Ac-LDL uptake, and migratory capacity as assessed by qRT-PCR, Western blotting, indirect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 54 publications
4
71
0
2
Order By: Relevance
“…82 Though it has been shown that exogenous VEGF application to wounds can stimulate angiogenesis, 83 MSCs used in cell therapeutics also have been shown to stimulate EC recruitment and wound healing via VEGF secretion 33,75 or via pre-differentiation into angiogenic precursors. 84 Ultimately, MSCs are able to stimulate de novo angiogenesis in wound beds upon transplantation, a crucial factor in stimulating healing in chronic wounds that lack this normally due to the hyperinflammatory environment.…”
Section: Stimulation Of Angiogenesismentioning
confidence: 99%
“…82 Though it has been shown that exogenous VEGF application to wounds can stimulate angiogenesis, 83 MSCs used in cell therapeutics also have been shown to stimulate EC recruitment and wound healing via VEGF secretion 33,75 or via pre-differentiation into angiogenic precursors. 84 Ultimately, MSCs are able to stimulate de novo angiogenesis in wound beds upon transplantation, a crucial factor in stimulating healing in chronic wounds that lack this normally due to the hyperinflammatory environment.…”
Section: Stimulation Of Angiogenesismentioning
confidence: 99%
“…According to the BBB disruption, we could not exclude the involvement of peripheral cell immunity even if we previously excluded the lymphocytic inflammatory reaction (4) that could be explained by the low immunogenicity of cord blood cells (16,17). Additionally, we previously reported that ECFCs did not proliferate and that only a few cells were visible 14 d after transplantation (4).…”
Section: Discussionmentioning
confidence: 99%
“…MI was achieved as described previously [19]. In brief, the mice were anesthetized with a mixture of O 2 /isoflurane (2%) (Baxter International Inc., Deerfield, IL, http://www.baxter.com), intubated, and mechanically ventilated (90 breaths per minute, 0.1 ml tidal volume) using a SAR830/AP small animal ventilator (CWE, Inc., Ardmore, PA, http://www/cwe-inc.com).…”
Section: Model and Delivery Of The Fibrin-cell Patchmentioning
confidence: 99%